Interes prawny a proces kościelny. Glosa aprobująca do wyroku Naczelnego Sądu Administracyjnego z dnia 08 maja 2015 r., II OSK 2416/13 - Niemczycki, Dawid (Ius Matrimoniale, 2020)
This gloss concerns the judgment of the Supreme Administrative Court of 8 May 2015, case II OSK 2416/13, in which the court stated that the legal interest conditioning the disclosure of personal data may be enjoyed not only in a trial before a secular court, but also in proceedings before ecclesiastical court. The gloss layout includes the introduction, the thesis of the order, premises of the factual and legal status, arguments of the Supreme Administrative Court, evaluation of the judgment and the conclusion. The author fully shares the justification of the judgment. Moreover, he points to the ground-breaking approach to the process of nullity of marriage before the ecclesiastical court, which is the basis for granting a legal interest in the procedure of disclosing personal data before a public administration body.